Compatibility between cold-natured medicine CP and hot-natured medicine AZ synergistically mitigates colitis mice through attenuating inflammation and restoring gut barrier. (1st March 2023) - Li, Yan-Yang; He, Yue-Xian; Wu, Ye-Qun; Liu, Chang; Ren, Ling-Zhi; Lu, Xiang-Yi; Wang, Yu-Mei; Yu, Yang
Abstract: Ethnopharmacological relevance: Ulcerative colitis (UC) is a nonspecific intestinal inflammation with complex pathogenesis. Traditional Chinese Medicine (TCM) formula consists of several TCM herbs following the principle of herbal property and compatibility. Our previous studies found that Huanglian Ganjiang decoction (HGD) exhibited anti-colitis capacity and the compatibility between hot-natured medicine and cold-natured medicine was main compatibility. However, the association between compatibility mechanism of HGD and its anti-colitis effect has not been fully illustrated yet. Aim of study: Here, we would explore whether cold-natured medicine Coptis chinensis Franch. plus Phellodendron chinense C.K.Schneid. (CP) and hot-natured medicine Angelica sinensis (Oliv.) Diels plus Zingiber officinale Roscoe (AZ) in HGD respectively produce different impacts on UC, and exert synergistic effect on UC together. Materials and methods: UPLC/MS-MS was used to qualitatively analyze chemical profiles of CP, AZ and CPAZ extracts. CPAZ-UC target network was constructed using network pharmacology. Colitis mice was induced by 3% DSS for 7 days and treated with CP, AZ and CPAZ for another 7 days. The levels of multiple cytokines and proportions of innate and adaptive immune cells were determined to assess inflammatory profiles. The leakage of FITC-dextran, expressions of tight junction proteins were detected for evaluation of gut barrier function. Results: CP, AZ and CPAZ could improve symptoms of colitis mice. CP showed superiority in reducing proportions of pro-inflammatory immune cells M1 cells, neutrophils, Th1 and Th17 cells, and levels of pro-inflammatory cytokines IFN-γ, IL-6, IL-10, TNF-α. In the contrast, AZ had advantage of elevating ratios of anti-inflammatory immune cells M2 and Treg cells as well as the production of anti-inflammatory cytokines IL-10 and TGF-β. In addition, CP and AZ synergistically regulated M1/M2 macrophage polarization and the following IL-6, IL-10, TNF-α, IFN-γ production, thereby restoring intestinal mucosal barrier. Conclusion: Taken together, our study first demonstrated that cold-natured medicine CP and hot-natured medicine AZ took on different functions in treatment of colitis mice. Meanwhile, they exhibited synergistic effect on the alleviation of intestinal inflammation and reinforcement of gut barrier function and integrity. Graphical abstract: Image 1 Highlights: Compatibility between cold-natured medicine CP and hot-natured medicine AZ synergistically exerted therapeutical effect on colitis mice. The compatibility mechanism between CP and AZ might be associated with synergistic reduction of intestinal inflammation and reinforcement of barrier function. CP showed superiority in reducing pro-inflammatory immune cells and pro-inflammatory cytokines. AZ had advantage of elevating anti-inflammatory immune cells and anti-inflammatory cytokines.